2011
DOI: 10.1002/rcm.4962
|View full text |Cite
|
Sign up to set email alerts
|

Improving peptide fragmentation by N‐terminal derivatization with high proton affinity

Abstract: An improved method of de novo peptide sequencing based on mass spectrometry using novel N-terminal derivatization reagents with high proton affinity has been developed. The introduction of a positively charged group into the N-terminal amino group of a peptide is known to enhance the relative intensity of b-ions in product ion spectra, allowing the easy interpretation of the spectra. However, the physicochemical properties of charge derivatization reagents required for efficient fragmentation remain unclear. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…8) among four structures used in this study, in which d b6 -ion was also observed. is is consistent with the previous observations that an Arg residue, which has a guanidino group in its side chain, at or near the N-terminus has the most signi cant in uence on generation of d-ions compared to other basic residues such as Lys and His.…”
Section: ) Bmentioning
confidence: 84%
See 3 more Smart Citations
“…8) among four structures used in this study, in which d b6 -ion was also observed. is is consistent with the previous observations that an Arg residue, which has a guanidino group in its side chain, at or near the N-terminus has the most signi cant in uence on generation of d-ions compared to other basic residues such as Lys and His.…”
Section: ) Bmentioning
confidence: 84%
“…8) It is known that a guanidino group of an Arg residue has high proton a nity, which retains a proton on that residue to generate d-ions by charge-remote fragmentation under HE-CID conditions if it exists at or near the N-terminus. 9) is suggests that the N-terminal derivatization with the structures having high proton a nity may facilitate the side-chain fragmentation to discriminate between Leu and Ile under HE-CID conditions in addition to its improvement e ect on fragmentation under LE-CID conditions.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…Of the structures tested, 4-amidinobenzoic acid (Aba) was found to have the appropriate proton affinity to serve as both a donor and an acceptor of mobile protons, which would provide "readable" fragmentation by increasing the number and intensity of b-ions. 9) However, some y-ions were still observed for cases of peptides containing highly basic residues even after derivatization, in which doubly-charged ions were selected as a precursor. This could lead to the incorrect assignment of b-ions in some cases.…”
Section: )mentioning
confidence: 99%